The Relativistic Outflow Driven by the Large-scale Magnetic Field from an Accretion Disk - Wei Xie; Wei-Hua Lei (The Astrophysical Journal)
Outflows/jets are ubiquitous in a wide range of astrophysical objects, yet the mechanisms responsible for their generation remain elusive. One hypothesis is that they are magnetically driven. Based on general relativistic MHD equations, we establish a formulation to describe the outflows driven by large-scale magnetic fields from the accretion disk in Schwarzschild spacetime. The outflow solution manifests as a contour level of a “Bernoulli” function, which is determined by ensuring that it passes through both the slow and fast magnetosonic points. This approach is a general relativistic extension to the classical treatment of X. Cao & H. C. Spruit. The initial plasma β that permits magnetically driven outflow solutions is constrained, with the slow magnetosonic point above the footpoint setting an upper limit ( β _b  ≲ 2) and the Alfvén point inside the light cylinder setting a lower limit ( β _b  ≳ 0.02). The higher the magnetization, the higher the temperature allowed, leading to relativistic outflows/jets. We investigate the relativistic outflows/jets of several typical objects, such as active galactic nuclei, X-ray binaries, and gamma-ray bursts. The results indicate that all of these phenomena require strongly magnetized, high-temperature outflows as initial conditions, suggesting a potential association between the production of relativistic outflows/jets and corona-like structures.